2012
DOI: 10.2106/jbjs.i.01403
|View full text |Cite
|
Sign up to set email alerts
|

Increased Use of Intramedullary Nails for Intertrochanteric Proximal Femoral Fractures in Veterans Affairs Hospitals

Abstract: Intramedullary nail use increased from 1998 through 2005 but did not decrease perioperative mortality or comorbidity compared with standard plate-and-screw devices for patients treated for intertrochanteric proximal femoral fractures in VA facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 19 publications
3
49
1
Order By: Relevance
“…Several authors have reported an increasing trend in the use of intramedullary devices to fix pertrochanteric fractures in patients with osteoporosis, despite the lack of supporting evidence. (4,(6)(7)(8)(9) Nonetheless, intramedullary fixation with both long and short cephalomedullary nails has been utilised with good clinical outcomes. (4,5,(10)(11)(12)(13) There are concerns regarding the use of long and short cephalomedullary nails in intramedullary fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported an increasing trend in the use of intramedullary devices to fix pertrochanteric fractures in patients with osteoporosis, despite the lack of supporting evidence. (4,(6)(7)(8)(9) Nonetheless, intramedullary fixation with both long and short cephalomedullary nails has been utilised with good clinical outcomes. (4,5,(10)(11)(12)(13) There are concerns regarding the use of long and short cephalomedullary nails in intramedullary fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Different surgical options exist yet the intramedullary hip screw (IMHS) has gained substantial popularity heralded for the improved biomechanical stability, less invasive surgical technique, shorter operative time, less blood loss, and earlier patient mobilization ( Fig. 1) [2][3][4][5][6]. Superior outcomes, however, have not been clearly reported with this device compared to more traditional techniques such as the sliding hip screw [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…With the growing number of IMHS being utilized, it is important to understand the potential downsides of its use [3,8]. The first generation IMHS was fraught with technical complications [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that in the United States, the incidence of hip fractures will increase from 1.2 million in 1990 to as many as 4.5 million in the year 2050; with intertrochanteric fractures making up approximately one half of these injuries [1][2][3][4]. While both fixed angle cephalomedullary nailing and extramedullary side plates can be used to treat intertrochanteric fractures, cephalomedullary nailing has gained popularity since its introduction in the 1980s [5][6][7]. Studies suggest that cephalomedullary nailing of intertrochanteric femur fractures may have shorter operating times, decreased blood loss, greater fixation stability, shorter inpatient times and potential protective effects with regard to possible future femur fractures [8][9][10].…”
Section: Introductionmentioning
confidence: 99%